2014
DOI: 10.1262/jrd.2014-031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Murine Pituitary-Derived Cell Lines Tpit/F1, Tpit/E and TtT/GF

Abstract: The pituitary is an important endocrine tissue of the vertebrate that produces and secretes many hormones. Accumulating data suggest that several types of cells compose the pituitary, and there is growing interest in elucidating the origin of these cell types and their roles in pituitary organogenesis. Therein, the histogenous cell line is an extremely valuable experimental tool for investigating the function of derived tissue. In this study, we compared gene expression profiles by microarray analysis and real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Several years ago, it was suggested that spindle cell oncocytomas represent the long-anticipated tumor of folliculostellate cytogenesis (Roncaroli et al 2002); however, these have now been shown to be derived from pituicytes of the posterior lobe (Mete et al 2013). The strong expression of NG2 in folliculostellate cells of the adenohypophysis noted in our study is consistent with the recent description of NG2 expression in the clonal TtT cell line that is thought to be derived from folliculostellate cells (Yoshida et al 2014). Nevertheless, it was quite unexpected that we found no evidence of proliferation or transformation of those cells in the mouse model.…”
Section: Discussionsupporting
confidence: 92%
“…Several years ago, it was suggested that spindle cell oncocytomas represent the long-anticipated tumor of folliculostellate cytogenesis (Roncaroli et al 2002); however, these have now been shown to be derived from pituicytes of the posterior lobe (Mete et al 2013). The strong expression of NG2 in folliculostellate cells of the adenohypophysis noted in our study is consistent with the recent description of NG2 expression in the clonal TtT cell line that is thought to be derived from folliculostellate cells (Yoshida et al 2014). Nevertheless, it was quite unexpected that we found no evidence of proliferation or transformation of those cells in the mouse model.…”
Section: Discussionsupporting
confidence: 92%